2011
DOI: 10.1007/s10585-010-9364-6
|View full text |Cite
|
Sign up to set email alerts
|

The dietary flavonoid apigenin enhances the activities of the anti-metastatic protein CD26 on human colon carcinoma cells

Abstract: There is accumulating evidence that secondary plant metabolites such as flavonoids may have anti-cancer properties, and yet the molecular pathways that lead to alterations in cancer cell behaviour remain unclear. We investigated the possible actions of apigenin, a flavone present in leafy vegetables like parsley, on the levels of CD26 in carcinoma cells. CD26 is a multifunctional cell-surface protein that through its associated dipeptidyl peptidase (DPPIV) and ecto-adenosine deaminase (eADA) enzyme activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 73 publications
3
56
0
Order By: Relevance
“…CD26/DPPIV is down-regulated in various cancers including colorectal carcinoma. Apigenin substantially upregulates CD26/DPPIV on human colorectal cancer HT-29 and HRT-18 cells to inhibit metastasis [81]. Synergistic interaction between apigenin and ABT-263, a BH3 mimetic inhibitor of the Bcl-2 family, was more potent than apigenin or ABT-263 alone in inhibiting tumor growth in xenograft tumors of colon cancer cells [82].…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…CD26/DPPIV is down-regulated in various cancers including colorectal carcinoma. Apigenin substantially upregulates CD26/DPPIV on human colorectal cancer HT-29 and HRT-18 cells to inhibit metastasis [81]. Synergistic interaction between apigenin and ABT-263, a BH3 mimetic inhibitor of the Bcl-2 family, was more potent than apigenin or ABT-263 alone in inhibiting tumor growth in xenograft tumors of colon cancer cells [82].…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…Research has shown that a reduction of MAPK leads to the inhibition of cell proliferation in human prostate cancer and apoptosis in anaplastic thyroid cancer. 36 Apigenin can also lower the concentrations of the enzymes aromatase and 17b-hydroxysteroid dehydrogenase. Breast and prostate cancer growth is inhibited by the influence of apigenin on estrogen receptor b-1.…”
Section: Impact On Cell Adhesion Moleculesmentioning
confidence: 99%
“…36 It plays an important role in hematological cancer where cell differentiation is inhibited at a particular stage in its maturation. Flavonoid apigenin-7-glucoside can induce acute myeloid leukemia HL-60 cells and chronic myeloid leukemia K562 cells to differentiate the granulocytic and the erythrocytic lineages, which is possible because apigenin increases the expression of alfa and gamma hemoglobin genes.…”
Section: Differentiation-induction Effectmentioning
confidence: 99%
“…The antitumour actions of apigenin are manifested through modulation of wide range of signalling molecules and their pathways. These include (a) inhibition of mTOR C2 (mammalian target of rapamycin complex-2) via downregulation of RICTOR expression (Guo, Zhou, Evers, & Wang, 2011), (b) decrease in mTOR and cyclin D1 expression (Turktekin et al, 2011), (c) increase in CD26 (cell surface protein), ecto-adenosine deaminase (ADA) binding (Lefort & Blay, 2011), (d) phosphorylation and upregulation of FADD (Fas associated protein with death domain) and expressions of cyclin D1, BAG-1, Bcl-2, yrd-C by acting on PKC δ (protein kinase C) and ataxia-telangiectasia mutated (ATM) kinases pathway (Zhong et al, 2010).…”
Section: Citrus Flavones In Colon Cancermentioning
confidence: 99%